Diplomatic Bluff against Indonesia’s G20 Presidency amid the Ukraine - Russia Conflict: A View from Political Psychology - Ogi Nanda Raka Ade Candra Nugraha; Arum Pramesti Wirawati; Muhammad Erwan Syah; Danang Prasetyo; Frega Ferdinand Wenas Inkiriwang (Cenderawasih University, 2022)
Political psychology has a pivotal role in the discipline of international relations, particularly in handling the conflict between Russia and Ukraine. The conflict severely affects all global aspects, from the economic to security, including Indonesia’s G20 Presidency. This study aims to analyze how political psychology contributes to reducing or becoming the key to the performance of the Indonesian G20 Presidency in conjunction with the Russia–Ukraine conflict and diplomatic bluff by some countries. With descriptive qualitative research methods, and data collection techniques with literature studies from books, journals, and webpage news, data were analyzed, and conclusions were drawn. The Russia–Ukraine conflict not only threatens international peace and security order but also challenges Indonesia’s G20 presidency as Russian Vladimir Putin gets invited to attend the summit. This article used the Tree Model, offering three mechanisms by prioritizing psychopolitics and psychoanalysis, which can be a reference for conflict resolution. This tree model is expected to be applied in response to the Russia–Ukraine conflict, bridge differences between all G20 members, and help Indonesia be well-prepared and successful for the summit.KEYWORDSDiplomatic Bluff; G20 Presidency; Political Psychology; Russia–Ukraine Conflict